Symbolism of Auto-Descriptions of Modern Human: Anthropology as a Narrative Ontology - Pavlo Kretov; Olena Kretova (International Society of Philosophy and Cosmology, 2018)
The purpose of the article is to investigate the content of the principal intentions of interpreting the symbol in the context of the anthropology of culture and philosophical anthropology and their correlation with the functioning of the semantic field of culture. The scientific originality of the article is presented by the study of the correlation between the consideration of the aspect of nature and the specificity of the symbol in autoscripting human practices within the philosophical projects representing these cognitive positions. The article substantiates the position on the ontologizing of the symbol in modern cultural and philosophical anthropology and the significance of convergence of the notion of the symbol with the concepts of the object and the thing. The cognitive potential of the conception of narrative ontology and its connection with the problematics of philosophical anthropology is emphasized. The importance of ontological turn in cultural anthropology for the philosophical anthropology is mentioned. The potential of the ontological turn in philosophical anthropology for the contemporary philosophy of education and comprehension of the newest ideological models interpreted as open and nonlinear systems is stressed. The correlation between the declared interpretation of the symbol and the project of object-oriented ontology and the modern philosophy of science is specifically considered. The conclusions of the article determine the specific character of being of the symbol in the communicative sphere of the modern man, social space, for the construction of identity and self-positioning of the modern individual.